Severe Pediatric Asthma Therapy: Mepolizumab - Ullmann, Nicola; Peri, Francesca; Florio, Olivia; Porcaro, Federica; Profeti, Elisa; Onofri, Alessandro; Cutrera, Renato (Frontiers in Pediatrics, 2022)
There is a growing need for advanced treatment in children with persistent and severe asthma symptoms. As a matter of fact, between 2% and 5% of asthmatic children experience repeated hospitalizations and poor quality of life despite optimized treatment with inhaled glucocorticoid plus a second controller. In this scenario, mepolizumab, a humanized monoclonal antibody, has proven to be effective in controlling eosinophil proliferation by targeting Interleukin-5 (IL-5), a key mediator of eosinophil activation pathways. Mepolizumab is approved since 2015 for adults at a monthly dose of 100 mg subcutaneously and it has been approved for patients ≥6 years of age in 2019. Especially in children aged 6 to 11 years, mepolizumab showed a greater bioavailability, with comparable pharmacodynamics parameters as in adult population. The recommended dose of 40 mg every 4 weeks for children aged 6 through 11 years, and 100 mg for patients ≥ 12 years provides appropriate concentration and proved similar therapeutic effects as in the adult study group. A marked reduction in eosinophil counts clinically reflects in a significant improvement of asthma control as demonstrated by validated questionnaires, reduction of exacerbation rates and number of hospitalizations. Finally, mepolizumab provides a safety and tolerability profile similar to that observed in adults with adverse events mostly of mild or moderate severity. The most common adverse events were headache and injection‐site reaction. In conclusion, mepolizumab can be considered a safe and targeted step-up therapy for severe asthma with an eosinophilic phenotype in children and adolescents.